Impact of COVID‐19 Pandemic on Children With Intellectual Disabilities and Their Parents: The Perspective of Parents in India. - Gogoi, Pariz Pikul; Jha, Munmun (British Journal of Learning Disabilities, 2025)
Background: The COVID‐19 pandemic affected children with intellectual disabilities and their parents in numerous ways. This study investigates the impact by analysing the narratives of their parents in the city of Guwahati, located in Assam, a northeastern state of India. The study contributes to the scholarship on intellectual disability in relation to the COVID‐19 pandemic. It suggests the central role of parents and the necessity of empowering them with timely information and disability training, which will help sustain the uninterrupted development of children. Methods: This study employs a qualitative method with semi‐structured interviews. Twelve parents of children with intellectual disabilities from three special schools participated in this study. The questions explored their lived experiences with their children, caregiving responsibilities at home and the challenges they faced due to the disruption of special services during the pandemic. Findings: Four key themes emerged from this study: (1) the pandemic led to the disruptions of special services for children with intellectual disabilities, (2) children's physical mobility was restricted at home, and they could not access regular need‐based therapies or exercise their social skills in special schools, (3) parents suffered psychological stress as they could not fathom how to manage the children at home and (4) parents underwent financial hardships due to their lack of resources and loss of family income during the pandemic. Conclusions: Parents emphasized the need for timely information regarding disability‐related measures to understand and deal with the risks of the pandemic. Some parents tried to engage their children in activities at home. This study recommends the strengthening of disability training for parents to limit the negative psychological effects and issues faced by children with intellectual disabilities. Future research should explore and unravel positive coping mechanisms used by the parents. Summary: This paper is about the experiences of parents with children with intellectual disabilities during the COVID‐19 pandemic.The sudden closure of special schools increased the difficulties in the overall learning process of the children.Easily accessible disability‐related services and information are required for children as well as parents during any health crisis.